2012
DOI: 10.1017/jmech.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Steady Flow Dynamics Study of Human Aortic Valve with Numerical Techniques

Abstract: Human aortic valve is made of thin collagen type tissue. The three leaflets open and close under fluid forces exerted upon them. To simulate the hemodynamic characteristics of the blood flow, ANSYS CFX10.0 software was utilized to analyze the three-dimensional Reynolds-averaged Navier-Stokes equations. With a quasi-steady analysis model, we predict values of the blood velocity and the wall shear stress both over the valve leaflets and the endothelial lining. In addition, investigation on fluid dynamic of a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, the extremely computation-intensive nature of the FSI method has constrained its application in dealing with large-scale models, which would take weeks to months to solve [62][63][64]. Compared with FSI simulation, the steady-state CFD simulation is advanced in providing a fast prediction of non-temporal flow characteristics with ease and has been widely used in the studies of valvular and aortic hemodynamics [65][66][67][68][69][70][71][72]. Despite the fact that the blood flow in the vascular system was pulsatile under physiological conditions, several numerical [73,74] and in vitro [75][76][77] studies have suggested that steady-state simulation can predict the non-temporal related flow characteristics at the corresponding point of the pulsatile flow profile.…”
Section: Modeling Simplificationsmentioning
confidence: 99%
“…However, the extremely computation-intensive nature of the FSI method has constrained its application in dealing with large-scale models, which would take weeks to months to solve [62][63][64]. Compared with FSI simulation, the steady-state CFD simulation is advanced in providing a fast prediction of non-temporal flow characteristics with ease and has been widely used in the studies of valvular and aortic hemodynamics [65][66][67][68][69][70][71][72]. Despite the fact that the blood flow in the vascular system was pulsatile under physiological conditions, several numerical [73,74] and in vitro [75][76][77] studies have suggested that steady-state simulation can predict the non-temporal related flow characteristics at the corresponding point of the pulsatile flow profile.…”
Section: Modeling Simplificationsmentioning
confidence: 99%